Transition metal catalyzed Olefin functionalization - Feng, Chao (2013)
This thesis describes transition metal (Pd, Rh, Cu) catalyzed olefin functionalization for the creation of new C-C bonds. Chapter 1 In chapter 1, the palladium-catalyzed bisolefination of alkynes are described. It not only offers a new synthetic pathway for the access of functionalized naphthalenes but also provide an instance of uncommon trans-carbopalladation for the reaction initiation. Chapter 2 In chapter 2, the cationic rhodium complex catalyzed olefination of phenol derivatives for the direct introdution of an α,β-unsaturated ester appendage is described. Deuterium labelling and kinetic isotope effect studies were performed to probe the reaction mechanism. Chapter 3 In chapter 3, rhodium-catalyzed hydroarylation of internal alkynes via C-H bond activation was described using N,N-dimethylaminocarbonyl as directing group. This protocol exhibits a wide spectrum of functionality compatibility because of the mild reaction condition employed and provides a highly effective synthetic method in the realm of C-H olefination. Chapter 4 In chapter 4, copper catalyzed olefinic trifluoromethylation and oxytrifluoromethylation of enamides were reported. The direct olefinic C-H trifluoromethylation constitutes an efficient method for the stereoselective synthesis of β-trifluoromethyl substituted enamides. Chapter 5 In chapter 5, palladium-catalyzed intermolecular C-H olefination of benzylamine derivatives employing bidentate system was described. Not only acrylate derivatives but also electron-neutral olefins could be employed, which further broaden the scope of palladium-catalyzed coupling reactions.